Identifying the season performance, workflow and analyse through car park site and office database survey and observation / Mohamad Azamuddin Abdul Karim - Abdul Karim, Mohamad Azamuddin (Faculty of Business and Management, 2010)
This study reveals on the performance of Season Unit under Finance Department. Season Unit comprises of seven season personnel who are responsible for updating customers’ payment, new application, refund matters and termination. They are also accountable to service existing customers, stock card control and other matters regarding season’s movements. Season users are car parks customers who subscribe the car parks to use every day by paying monthly, quarterly, semiannually and annually. These are considered as a fixed income to Metro Parking (M) Sdn Bhd as the mode of payment is guaranteed to be revenue. By receiving a high cash flow the company should possess a competitive advantage whereby a lot of investment activities can be done. Controlling the credit activity became the most essential elements in maximizing profits and negligence will affect the company’s performance in the long run as a whole. That is one of the reasons for conducting this research whereby I will identify the season department performance by conducting car park site and office database survey and observation. Comparison of data between site office and head will be made after the study has been conducted. Cash flow, customer payment, cancellation, termination, system data, application, monitoring list, detail aging and lock-out list will be analyzed thoroughly to ensure that the findings are reliable and accurate.